PENGARUH KINERJA PERUSAHAAN TERHADAP PENGHINDARAN PAJAK MELALUI UKURAN PERUSAHAAN PADA PERUSAHAAN LQ45 DI IDX - Aprilliana, Diar; Ajitama, Ombih; Rachman, Riza Aulia; Wahono, Puji; Pahala, Indra (Fakultas Ekonomi dan Bisnis, 2024)
This study is to determine the effect of company performance on tax avoidance seen from liquidity, profitability and company size which is used as mediation in tax avoidance. The samples used in this study are LQ45 companies listed on the Indonesia Stock Exchange in 2018 - 2022. The results of this study indicate that profitability and liquidity have no positive effect on tax avoidance. However, profitability and liquidity have a positive effect on company size. Meanwhile, company size does not mediate profitability and liquidity on tax avoidance in LQ45 companies listed on the Indonesia Stock Exchange.Key words: Tax Avoidence, Firm size, Liquidity, Profitability